2018
DOI: 10.1007/s10943-018-0596-0
|View full text |Cite
|
Sign up to set email alerts
|

Religion, Combat Casualty Exposure, and Sleep Disturbance in the US Military

Abstract: Does religious involvement (i.e., attendance and salience) mitigate the association between combat casualty exposure and sleep disturbance among US military veterans? To address this question, we analyze cross-sectional survey data from the public-use version of the 2011 Health Related Behaviors Survey of Active Military Personnel. Results from multivariate regression models indicate: (1) Combat casualty exposure was positively associated with sleep disturbance; (2) religious salience both offset and moderated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 66 publications
2
10
0
Order By: Relevance
“…Although previous studies have documented salutary associations between sleep outcomes and organizational and nonorganizational religious practices, we found no evidence that either of these dimensions of religious involvement mitigated the harmful consequences of stressful events on sleep. Our findings were therefore largely consistent with White et al.’s () aforementioned study of U.S. military personnel, which also failed to uncover any stress‐buffering effects of religious attendance on sleep quality. On the other hand, White et al.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Although previous studies have documented salutary associations between sleep outcomes and organizational and nonorganizational religious practices, we found no evidence that either of these dimensions of religious involvement mitigated the harmful consequences of stressful events on sleep. Our findings were therefore largely consistent with White et al.’s () aforementioned study of U.S. military personnel, which also failed to uncover any stress‐buffering effects of religious attendance on sleep quality. On the other hand, White et al.…”
Section: Discussionsupporting
confidence: 90%
“…In this study, we explore the possibility that each of these religious dimensions may moderate the association between stressful events and sleep. Although a small body of literature has linked religious factors with sleep outcomes in diverse samples (for a recent review, see Hill, DeAngelis, and Ellison 2018), the possible stress-buffering effects of religion on sleep appear to have been addressed only once, and only among a sample of active-duty U.S. military personnel (White et al 2018). In what follows, we explain why certain religious practices and cognitions should buffer the effects of major life events on sleep outcomes in the general U.S. population.…”
Section: The Stress-buffering Role Of Religious Practicesmentioning
confidence: 99%
See 1 more Smart Citation
“…A host of empirical studies has also shown that religious involvement can mitigate the adverse mental health effects of traumatic life events (DeAngelis and Ellison ; Ellison ), noxious neighborhood environments (Acevedo, Ellison, and Xu ; Krause ), financial hardship (Acevedo, Ellison, and Xu ; Bradshaw and Ellison ; Krause ), discrimination experiences (Ellison, DeAngelis, and Güven ; Ellison, Musick, and Henderson ), combat exposure (White et al. ), and failure to achieve salient life goals (DeAngelis ).…”
Section: Introductionmentioning
confidence: 99%
“…Over the past several decades, numerous studies have documented salutary associations between dimensions of religious involvement and various indicators of health and well-being, including subjective well-being (Ellison 1991;Lim and Putnam 2010), sleep quality (Hill, DeAngelis, and Ellison 2018), biological functioning (Hill et al 2014), cognitive functioning (Hill et al 2006), cellular aging (Hill et al 2016), and longevity (Hummer et al, 1999(Hummer et al, , 2004. A host of empirical studies has also shown that religious involvement can mitigate the adverse mental health effects of traumatic life events Ellison 1991), noxious neighborhood environments (Acevedo, Ellison, and Xu 2014;Krause 1998), financial hardship (Acevedo, Ellison, and Xu 2014;Krause 2003), discrimination experiences (Ellison, DeAngelis, and Güven 2017;Ellison, Musick, and Henderson 2008), combat exposure (White et al 2018), and failure to achieve salient life goals (DeAngelis 2018).…”
Section: Introductionmentioning
confidence: 99%